2020
DOI: 10.1002/solr.202000084
|View full text |Cite
|
Sign up to set email alerts
|

Insight on the Contribution of Plasmons to Gold‐Catalyzed Solar‐Driven Selective Oxidation of Glucose under Oxygen

Abstract: With the increasing concerns about pollution and reduction of energy demands, the use of solar energy to drive chemical transformations is becoming increasingly attractive. Within the context of sustainability, sunlight‐driven organic transformation of biomass feedstock, such as free carbohydrates, to obtain high added‐value products is an important topic in which the recent progress should contribute to the development of solar biorefineries. Among the variety of photocatalysts, gold nanoparticles (NPs) loade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Moreover the supporting material of the gold nanoparticles is known to affect the overall catalyst properties. Our previous experiences, as well as recent literature, showed that Au/CeO 2 exhibits excellent properties for aerobic oxidation of free sugars. For this reason, ceria was chosen as a support in this study.…”
Section: Resultsmentioning
confidence: 60%
See 1 more Smart Citation
“…Moreover the supporting material of the gold nanoparticles is known to affect the overall catalyst properties. Our previous experiences, as well as recent literature, showed that Au/CeO 2 exhibits excellent properties for aerobic oxidation of free sugars. For this reason, ceria was chosen as a support in this study.…”
Section: Resultsmentioning
confidence: 60%
“…Particularly, the oxidation of the anomeric position of free sugars using gold nanoparticles (Au NPs) as the catalyst has been widely investigated. In aqueous conditions using O 2 or H 2 O 2 as the oxidant, free sugars are selectively converted into corresponding aldonate salts or aldonic acids, identified as promising biobased chemical platforms to replace those currently derived from the petroleum . Among others, we contributed to this topic by demonstrating that alternative activation pathways such as microwave or photocatalysis were effective to enhance both the conversion yield and the reaction selectivity. Nevertheless, the subsequent transformation of the oxidized derivative (aldonic acid or aldonate salt) is unfavored due to the weak reactivity of the carbonyl group, for which an activating group is generally needed. Sugar lactones, activated derivatives, represent a viable alternative to overcoming this issue and are widely used as building blocks for glycoconjugate synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, either with CeO 2 alone or without catalyst, oxidative cleavage was observed instead of the desired controlled oxidation. [ 151 ] Moreover, conversion under irradiation is two times higher than that under dark conditions. Experimental evidence suggests that for this catalytic system, aerobic photocatalyzed oxidation of glucose is due to thermal effects and not to charge separation processes in CeO 2 or the generation of hot carriers on Au NPs.…”
Section: Photocatalytic Applicationsmentioning
confidence: 99%
“…Despite the decreased TOF after five cycles, the conversion and selectivity remained high, indicating excellent reusability of this catalyst. The use of O 2 as the oxidant was also studied for Au/CeO 2 -photocatalyzed glucose oxidation (Golonu et al, 2020). The reaction may be driven by the thermal effect induced by near-infrared radiation, instead of UV-promoted excitation of CeO 2 or visible photon-activated SPR effect of Au nanoparticles.…”
Section: Photo-catalytic Oxidationmentioning
confidence: 99%